Cesarean myomectomy: A case report in Zainoel Abidin General Hospital, Banda Aceh, Indonesia - Bram Pradipta; Mohd. Andalas (Syiah Kuala University, 2011)
The objective of the present study was to improve skill and knowledge in making a Cesarean myomectomy decision, its complications and its post operative care. Uterine myomas are the most common pelvic tumors over the age of 30. The incident of myomas in pregnancy are 0.05-5%.Myomas are now more frequently seen as many women delaying childbearing which is the time for greatest risk of myoma growth. Also the use of ultrasonography has improved the diagnostic capability of detecting small myomas and has increased our knowledge of myomas in pregnancy. Myomectomy during cesarean section has traditionally been discouraged because of the risk of uncontrollable hemorrhage. There are approximately 7 choices to be made according cesarean myomectomy such to leave it be, to leave it with Uterine artery ligation, to remove pedunculated fibroids only, to remove pedunculated, anterior subserous or lower uterine segment fibroids, to remove all anterior uterine fibroids, to remove all fibroids and selective removal of fibroids. A 32- year-old, gravida 3 para 2, Indonesian women presented with postterm-pregnancy and 20 cm intra mural- uterine myoma. Cesarean myomectomy was done to her with little to none intraoperative hemorrhage. Post C-section we found complications shown by uterine atony, profuse bleeding seen at the drainage through the peritoneum and marked changes in hemoglobin value. It is then carefully evaluated and managed using extensive follow up, high dose oxytocyin and blood transfusion. Cesarean myomectomy is now considered by many not always as a hazardous procedure and can be performed in experienced hands, in a well equipped tertiary institution, with the advent of better anesthesia, with availability of blood, in selected patients and according to site and size of myomas. It is always important to have a good informed consent beforehand and post operative care of cesarean myomectomy